Phosphate Precipitates and Water-Soluble Aggregates in Re-analyzed Solubility-pH Data of Twenty-five Basic Drugs - Alex Avdeef (International Association of Physical Chemists (IAPC), 2014)
The purpose of the study was to assess the stoichiometries of phosphate precipitates and determine the intrinsic solubilities, S0, of 25 basic drugs from their published solubility-pH profiles in the landmark study of Bergström et al. (2004), where 0.15 M phosphate buffer media had been used. A secondary purpose of this study was to attempt to predict phosphate 1:1 and 2:1 solubility products, Ksp, from knowledge of S0. The published data have been re-analyzed using a novel solubility-pH analysis computer program, pDISOL‑XTM. The program internally derives implicit solubility equations, given a set of proposed equilibria and constants (which are then iteratively refined by weighted nonlinear regression), and does not require explicit Henderson-Hasselbalch equations. The data were tested for the presence of phosphate precipitates of various stoichiometries, as well as the simultaneous presence of aggregated species, either cationic or neutral. The presence of particular species was suggested by the slope characteristics of the log S vs. pH curves. Considerably different intrinsic solubility constants were found, compared to those originally reported, for several drugs (e.g., celiprolol, desipramine, haloperidol). The least soluble molecule, amiodarone, analyzed to have the extraordinarily low intrinsic solubility of 2 picograms/mL, a moderate salt solubility of 0.82 mg/mL at the Gibbs‑pKa 5.4, corresponding to the species BH∙H2PO4(s), and a substantial presence of the positively-charged pentameric aggregate, (BH)5.